PELUANG DAN TANTANGAN FINTECH SYARIAH UNTUK UMKM DI KABUPATEN SIDOARJO - Suryono Suryono; Inggar Rizki Bintang Wijoyo; Fara Diah Pitaloka; Pradhipa Haqi Santoso; Rizkiani Ilfiana Putri; Harman Ago (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the Opportunities and Challenges of Fintech Syariah for UMKM in Sidoarjo Regency. This research uses qualitative descriptive research. The method used is a qualitative method. Data collection methods were carried out by interviews and observation. Data analysis method the data sources used in this research are primary and secondary data sources. Primary data sources can be obtained from interviews. Meanwhile, secondary data sources were obtained through literature study with the help of print media and internet media. Fintech Syariah is a combination of innovation in the fields of finance and technology that facilitates transaction and investment processes based on sharia values. Even though Fintech is a new breakthrough, it is experiencing rapid development. Fintech brings great opportunities and potential in the development of UMKM in Indonesia. In general, UMKM have difficulties in financial and capital aspects. The existence of fintech can help UMKM to gain convenience and efficiency in the financial aspect. The results of this research show that the Opportunities and Challenges of Fintech Syariah for UMKM in Sidoarjo Regency are still less popular among business actors. The reason is because they don't know yet, no one is interested, and they are afraid of the rise in fraud cases. Therefore, the OJK must be more selective regarding the many types of fintech that exist around us.